Patient Perceptions of Electronic Medical Record Use by Doctors in GMC Health Center Clinic - Ismil Khairi Lubis; Annisa Maulida Ningtyas; Nurfillaeli Nurfillaeli (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Effective communication between doctor and patient is needed to obtain optimal results for patient recovery. The GMC Health Center clinic applies Electronic Medical Records (EMR) to support comprehensive health services. EMR has a positive impact on doctors but is not so felt by patients. This study aims to analyze patient perceptions of EMR use by doctors in GMC Health Center Clinic. This research is an analytic survey with a cross-sectional design. Sampling by accidental sampling with a total of 91 patients. Research variables include patient perceptions of the use of EMR by doctors and patient satisfaction. Data analysis was carried out in univariate and bivariate with the Pearson Product-Moment correlation test using SPSS Software. The results showed that patients who were satisfied with the use of EMR by doctors mostly had a positive perception of EMR (76.6%). Pearson Product-Moment correlation test showed that there was a significant relationship between patients' perceptions of the use of EMR with patient satisfaction (p-value<α=0.05; r=0.689). The perception of the EMR communication function has a greater correlation with patient satisfaction (72%) than the perception of the clinical function of EMR (48.2%). The conclusion is patients have a positive perception of the use of EMR by doctors and also proven by the high level of patient satisfaction. Doctors should continue to improve communication and focus on patients when using EMR. Keyword: Electronic Medical Records, Patient, Perception ,